2016
DOI: 10.1093/bja/aew246
|View full text |Cite
|
Sign up to set email alerts
|

Improved postoperative oxygenation after antagonism of moderate neuromuscular block with sugammadex versus neostigmine after extubation in ‘blinded’ conditions

Abstract: In summary, this meta-analysis suggests that the PVI could be an accurate predictor of fluid responsiveness in children under mechanical ventilation in the operating theatre. In the future, this non-invasive haemodynamic monitoring tool could be incorporated into an intraoperative fluid management algorithm in the paediatric population. However, given the low number of studies and participants and the heterogeneity among studies in terms of sensitivity, additional studies are required to confirm our findings b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Numerous studies have investigated the in uence of NMB in respiratory outcome after anesthesia, and neostigmine was shown to have direct detrimental effects [25]. In contrast, other studies reported that after administration of NMB, sugammadex was associated with fewer postoperative adverse respiratory events [26][27]. In this study, administration of sugammadex was associated with fewer PPCs, such as postoperative cough, pleural effusion (all), massive pleural effusion and breathing failure in patients with pulmonary dysfunction before operation.…”
Section: Discussionmentioning
confidence: 58%
“…Numerous studies have investigated the in uence of NMB in respiratory outcome after anesthesia, and neostigmine was shown to have direct detrimental effects [25]. In contrast, other studies reported that after administration of NMB, sugammadex was associated with fewer postoperative adverse respiratory events [26][27]. In this study, administration of sugammadex was associated with fewer PPCs, such as postoperative cough, pleural effusion (all), massive pleural effusion and breathing failure in patients with pulmonary dysfunction before operation.…”
Section: Discussionmentioning
confidence: 58%
“…Initial evidence from a retrospective study shows that sugammadex reversal was associated with reduced incidence of pulmonary complications in elderly ASA three and four patients compared to reversal with neostigmine 47 . In a small prospective study, sugammadex reversal was associated with fewer hypoxemic events in the PACU compared to neostigmine reversal 39 . The current evidence is far from complete, and future prospective studies should determine the exact value of sugammadex in improving post-anesthesia pulmonary outcome.…”
Section: Prevention Of Postoperative Residual Curarizationmentioning
confidence: 93%
“…A recent investigation reported a 0% PORC rate in patients reversed with sugammadex versus 46% in those who received neostigmine 43 . These results are promising; however, in an unmonitored setting, PORC after sugammadex reversal still occurred in 4% of patients 36 , 39 , 44 . This highlights the need for adequate neuromuscular monitoring in any setting where NMBAs are used, regardless of the type of reversal agent.…”
Section: Prevention Of Postoperative Residual Curarizationmentioning
confidence: 96%
See 2 more Smart Citations